2020
DOI: 10.1044/2019_ajslp-19-00162
|View full text |Cite
|
Sign up to set email alerts
|

Using Crowdsourced Listeners' Ratings to Measure Speech Changes in Hypokinetic Dysarthria: A Proof-of-Concept Study

Abstract: Purpose Interventions for speech disorders aim to produce changes that are not only acoustically measurable or perceptible to trained professionals but are also apparent to naive listeners. Due to challenges associated with obtaining ratings from suitably large listener samples, however, few studies currently evaluate speech interventions by this criterion. Online crowdsourcing technologies could enhance the measurement of intervention effects by making it easier to obtain real-world listeners' rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
1
5
0
1
Order By: Relevance
“…Although recent evidence has demonstrated the efficacy of crowdsourced perceptual tasks completed on personal equipment (Nightingale et al . 2020), further studies may benefit from controlling such factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although recent evidence has demonstrated the efficacy of crowdsourced perceptual tasks completed on personal equipment (Nightingale et al . 2020), further studies may benefit from controlling such factors.…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase participation of listeners, the intelligibility assessment was conducted on a Google‐based platform (see Nightingale et al . 2020 for a similar remote platform). Upon entry to this online task, listeners reported basic demographic information, and were presented with detailed instruction regarding the listening task.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the impact of increased vocal intensity/loudness on speech intelligibility for people with PD in quiet listening conditions during un-cued speech tasks following intensive voice treatment [89][90][91]. In these studies, increased vocal loudness was found to increase intelligibility in PD participants for words extracted from read sentences [91], reading of passages [90], and conversational monologue [89].…”
Section: Loudness and Intelligibilitymentioning
confidence: 99%
“…Für die Rekrutierung von Laienhörer(inne)n zur auditiven Bewertung von Sprechstörungen ist Online-Crowdsourcing eine vielversprechende Methode (Überblick in [5]). Das Verfahren wurde auch in der Dysarthrieforschung bereits erfolgreich eingesetzt [6]. Dabei konnte die Validität der Urteile im Vergleich zu Bewertungen unter Laborbedingungen nachgewiesen werden [7].…”
Section: Online-crowdsourcing Bringt Die Umwelt In Den Therapieraumunclassified